Benzamil sensitive ion channels contribute to volume regulation in canine chondrocytes - Lewis, R.; Feetham, C.H.; Gentles, L.; Penny, J.; Tregilgas, L.; Tohami, W.; Mobasheri, Ali; Barrett-Jolley, Richard (Wiley, 2013)
Background and Purpose: Chondrocytes exist within cartilage and serve to maintain the extracellular matrix. It has been postulated that osteoarthritic (OA) chondrocytes lose the ability to regulate their volume, affecting extracellular matrix production. In previous studies, we identified expression of epithelial sodium channels (ENaC) in human chondrocytes, but their function remained unknown. Although ENaC typically has Na+ transport roles, it is also involved in the cell volume regulation of rat hepatocytes. ENaC is a member of the degenerin (Deg) family, and ENaC/Deg-like channels have a low conductance and high sensitivity to benzamil. In this study, we investigated whether canine chondrocytes express functional ENaC/Deg-like ion channels and, if so, what their function may be.